The Literary Style of Javanese Female Characters in the Novel Jemini by Suparto Brata (Universitas Negeri Semarang, 2020)
Women in the journey of human life have an important role, namely; give birth, nurture and educate their children. Mental education for women began to be developed, one of them through literary novels. The Novel Jemini by Suparto Brata presents the femininity of Javanese women from an objective point of view. Another interesting part of the novel is the strong characterization of Javanese women. This is emphasized by the use of various styles of language and diction which aim to uncover the struggle for life of Javanese women leaders. The objectives of this study are (1) Describe the characterization of Javanese women in the novel Jemini by Suparto Brata; (2) Uncovering the struggle for life of Javanese female characters in the novel Jemini by Suparto Brata; (3) Describing the lliterary style of Javanese female characters in the novel Jemini by Suparto Brata. This literary research uses the approach of feminism which is sulking in the Javanese feminism model. The data used in the form of fragments of text in the novel Jemini by Suparto Brata contained the characterization of Javanese women. Source of text data in the novel as a whole. The study’s method is semiotic structuralism with hermeneutic techniques. The results of this study indicate the feminism of Javanese women in the characterization of the novel Jemini by Suparto Brata. The lliterary style of the female characters in the novel consists of; words, sentences, phrases, figurative languages ​​show the existence of feminism in the novel Jemini by Suparto Brata. The character of Javanese women in the novel is clever, broad-minded, always curious, shy, agile, nimble, diligent in working, strong-minded, patient and accepting, sympathetic, respectful towards parents, and adults.This research raises awareness for the public about the role of women.